(3fXjQI CWhGb GdPgHs ((3GdeOjfI GdefhQI s)
(3ChdgG (B:s
(3Gddge EfG fMeOc Ydi eG CSHdJ ef LdGHjH cQec, ef TBHjH fYec, hfTcQc Ydi eG CaOJ ef cdeGJc GdJGeI s
(3BNQgG (B:s
(3heG PGc EdG CRGgjQ oYQVJ Ydjg ef CZUGf GdZjH, aTegf, hWjhQ aUGM JaQbJ CLRGDgG Ydi LHGd GdbOS aVegf s
(3CWhGb GdPgH ddReNTQjs
(3HgG fXGe GdJYbjHIs
(3Hjf GdSWhQ TQhM heYGfs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs